2002
DOI: 10.1152/ajpgi.00268.2001
|View full text |Cite
|
Sign up to set email alerts
|

Transport of ketone bodies and lactate in the sheep ruminal epithelium by monocarboxylate transporter 1

Abstract: Due to intensive intracellular metabolism of short-chain fatty acids, ruminal epithelial cells generate large amounts of D-beta-hydroxybutyric acid, acetoacetic acid, and lactic acid. These acids have to be extruded from the cytosol to avoid disturbances of intracellular pH (pH(i)). To evaluate acid extrusion, pH(i) was studied in cultured ruminal epithelial cells of sheep using the pH-sensitive fluorescent dye 2',7'-bis(2-carboxyethyl)-5(6)-carboxyfluorescein. Extracellular addition of D-beta-hydroxybutyrate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 26 publications
(49 reference statements)
9
106
2
Order By: Relevance
“…Maintenance of rumen intracellular pH is accomplished partly through exchange proteins, such as Na 1 /H 1 exchange (NHE) proteins and MCT1 that regulate cellular H 1 efflux (Gä bel and Aschenbach, 2006) and transport of SCFA metabolites into the blood (Mü ller et al, 2002), respectively. The NHE proteins, in concert with Na 1 /K 1 -ATPases (Albrecht et al, 2008), counteract the increase in H 1 concentration in the cytosol during transport of SCFA into the rumen epithelium (Mü ller et al, 2000).…”
Section: Maintenance Of Rumen Phmentioning
confidence: 99%
See 3 more Smart Citations
“…Maintenance of rumen intracellular pH is accomplished partly through exchange proteins, such as Na 1 /H 1 exchange (NHE) proteins and MCT1 that regulate cellular H 1 efflux (Gä bel and Aschenbach, 2006) and transport of SCFA metabolites into the blood (Mü ller et al, 2002), respectively. The NHE proteins, in concert with Na 1 /K 1 -ATPases (Albrecht et al, 2008), counteract the increase in H 1 concentration in the cytosol during transport of SCFA into the rumen epithelium (Mü ller et al, 2000).…”
Section: Maintenance Of Rumen Phmentioning
confidence: 99%
“…At the protein level, immunohistochemistry (IHC) studies indicated localized expression of the MCT1 protein almost exclusively in the stratum basale of the stratified epithelial layers of the rumen (Mü ller et al, 2002;Graham et al, 2007) and diffuse, weak staining for MCT2 in the three epithelial layers beneath the stratum corneum (Graham et al, 2007). Using primary cultures of ovine ruminal epithelium treated with b-hydroxybutyrate, acetoacetate and lactate with and without competitive blockers of MCT1, Mü ller et al (2002) demonstrated MCT1-mediated uptake of ketone bodies and lactate. Their uptake was associated with a drop in intracellular pH.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of these SCFA (which consist mainly of acetate (,60%), propionate (,20%) and butyrate (,10%) are absorbed across the forestomachs and cover a substantial part of the animals energy requirements (Bergman, 1990). The major fraction of SCFA crosses the forestomach epithelia unmetabolized (Kiddle et al, 1951;Gä bel et al, 2002), although SCFA, in particular butyrate, are also used by the epithelial cells themselves for cell metabolism, which could support active transport of other electrolytes (Weigand et al, 1975;Sehested et al, 1999;Kristensen et al, 2000;Gä bel et al, 2002;Gä bel and Aschenbach, 2006). Apical uptake mechanisms for SCFA Previous studies and reviews have focussed on two possible mechanisms of SCFA uptake across the apical membrane: diffusion of the protonated, undissociated form through the lipid bilayer and exchange of the dissociated SCFA 2 anion for bicarbonate via a transport protein that exchanges SCFA 2 for HCO 3 2 anions under physiological conditions (Figure 4, Gä bel et al, 1991a;Kramer et al, 1996;Gä bel et al, 2002;Aschenbach et al, 2009).…”
Section: Absorption Of Scfasmentioning
confidence: 99%